THE EFFECT OF DIFFERENT FEEDING METHODS ON THE GROWTH AND DEVELOPMENT OF MELON VARIETIES - Kalantarov Sanat Kadamboyevich; Sadullayev Sanjarbek Madiyarovych (Galaxy International Interdisciplinary Research Journal, 2023)
In this article, it was found that the number and weight of fruits per plant in the variants with 18 kg of hydrogel per hectare were higher than the control variant. Based on the obtained results, the varieties with high performance are indicated.